Evaluation of micropropagated plantain and banana (Musa spp.) for banana streak badnavirus incidence under field and screenhouse conditions in Nigeria - Dahal, G.; Gauhl, F.; Pasberg-Gauhl, C.; Hughes, J.D.A.; Thottappilly, G.; Lockhart, B.E.L. (1999)
Between 1991 to 1996, more than 50 Musa hybrids and 10 landraces were evaluated under field and screenhouse conditions for virus symptoms resembling those caused by banana streak badnavirus (BSV). The symptoms included chlorotic streaks, leaf deformation, stunting, cigar leaf death, distortion of the peduncle, bunch or fruits, and internal pseudostem necrosis. Immunosorbent electron microscopy (ISEM) of randomly selected plants with one or more of these symptoms confirmed the presence of BSV particles in 15 tropical Musa plantain hybrids (TMPx) and five Musa landraces. Under both field and screenhouse conditions, the incidence of symptomatic plants in the hybrids was significantly higher than in the landraces. The hybrids also generally had a higher concentration of BSV antigens, as determined by enzyme‐linked immunosorbent assay (ELISA). By contrast, most BSV‐infected landraces were symptomless and had very low or undetectable amounts of BSV antigens. There was a significant variation in incidence of symptomatic plants between genotypes, experiments and year of observation. These results are discussed in relation to the higher natural BSV incidence observed on some Musa hybrids as compared with their parental genotypes.